Effect of Kangaroo Mother Care (KMC) and Touching Therapy Techniques on Weight Gain in LBW Infants - Dewi, Nur Avni Atikah; Indarwati, Ferika; Sustieni, Sri (LPPM STIKes Muhammadiyah Ciamis, 2025)
Low Birth Weight (LBW) infants are at higher risk for developmental delays, stunting, and increased morbidity. Non-pharmacological interventions such as Kangaroo Mother Care (KMC) and Touching Therapy have been shown to improve the physical growth and emotional well-being of LBW infants. This case study aims to evaluate the effect of Kangaroo Mother Care (KMC) combined with Touching Therapy on weight gain in an infant with Very Low Birth Weight (VLBW). A single-case report was conducted on a neonate diagnosed with severe asphyxia and VLBW (birth weight 1130 grams) at RSUD Tidar Magelang. The intervention consisted of KMC and Touching Therapy sessions performed for 2 hours daily over six consecutive days. Body weight was measured before and after each intervention to assess daily changes. The infant's weight increased steadily from 1266 grams on day one to 1397 grams on day six, resulting in a total weight gain of 131 grams. This suggests that the combination of KMC and Touching Therapy may support short-term weight gain in VLBW infants. The findings demonstrate a notable improvement in body weight following six days of combined KMC and Touching Therapy. These interventions may be recommended to parents and caregivers both in clinical and home settings to promote healthy growth in LBW infants.